2019
DOI: 10.15376/biores.14.2.4603-4622
|View full text |Cite
|
Sign up to set email alerts
|

Response surface optimization of ammonium sulfite pretreatment for fermentable sugar production from wheat straw

Abstract: The development of a clean and sustainable pretreatment is of great importance for the production of fermentable sugars. In this study, an ammonium sulfite (AS) pretreatment of wheat straw was optimized based on response surface methodology with a three-level, three-factor Box-Behnken design. The investigated factors were AS dosage, pretreatment time, and pretreatment temperature. The effectiveness of the AS pretreatment was evaluated using the standard enzymatic hydrolysis procedure. A second-order polynomial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The stretching of the aromatic core in lignin is observed at peaks with the value 1595 and 1510 cm −1 . These signals describe the aromatic vibrations characteristic of lignin syringyl and guaiacyl type [18,19]. Subsequently, to further confirm our hypothesis, we left the dioxane solution with dissolved brown fragments to dry in the oven.…”
Section: Characterization Of Obtained Pulp After Rotary Experimentssupporting
confidence: 52%
See 3 more Smart Citations
“…The stretching of the aromatic core in lignin is observed at peaks with the value 1595 and 1510 cm −1 . These signals describe the aromatic vibrations characteristic of lignin syringyl and guaiacyl type [18,19]. Subsequently, to further confirm our hypothesis, we left the dioxane solution with dissolved brown fragments to dry in the oven.…”
Section: Characterization Of Obtained Pulp After Rotary Experimentssupporting
confidence: 52%
“…Subsequently, we compared the isolated lignin from the leachate with the lignin obtained from the fibers (Figure 6). Observing the absorbance at a wavenumber of 897 cm −1 and 1055 cm −1 characteristic for cellulose, we see smaller values compared to the original biomass [19]. We observe the same at a wavelength of 1247 cm −1 .…”
Section: Characterization Of Obtained Pulp After Rotary Experimentsmentioning
confidence: 52%
See 2 more Smart Citations
“…Pretreatment is crucial in cellulosic ethanol production, and the selection of an ideal pretreatment strategy is based on economic feasibility, environmentally benign, its ability to improve enzymatic hydrolysis efficiency, avoid degradation of carbohydrates, and prevent the release of compounds that inhibit subsequent saccharification and fermentation [5]. Several laboratory and pilot-scale investigations have reported that chemical and some thermal pretreatment methods led to high enzymatic hydrolysis efficiency [6][7][8][9]. However, these methods are limited by high energy input and the use or release of harmful substances associated with the process.…”
Section: Introductionmentioning
confidence: 99%